2008
DOI: 10.35536/lje.2008.v13.i2.a2
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effectiveness of Financial Development in Pakistan

Abstract: This study attempts to discern the relationship between economic and financial development in Pakistan for the period 1973 -2006. Vector error-correction modeling is used to identify the causality between economic and financial development and the exogeneity of the variable(s) in the model. These error correction terms have been derived from Johansen's multivariate cointegrating procedure. Results indicate that, in the long run, economic development causes financial development. Furthermore, the real output va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…With respect to Pakistan, the majority of studies (for instance, Khan, Qayyum, & Sheikh, 2005;Tahir, 2008;Khan, 2008;Jalil & Ma, 2008;Rehman & Cheema, 2013;Naveed & Mahmood, 2019) used linear modeling technique to investigate finance-growth nexus. However, these studies ignored the asymmetric relationship, while investigating finance-growth nexus.…”
Section: Model Data and Methodologymentioning
confidence: 99%
“…With respect to Pakistan, the majority of studies (for instance, Khan, Qayyum, & Sheikh, 2005;Tahir, 2008;Khan, 2008;Jalil & Ma, 2008;Rehman & Cheema, 2013;Naveed & Mahmood, 2019) used linear modeling technique to investigate finance-growth nexus. However, these studies ignored the asymmetric relationship, while investigating finance-growth nexus.…”
Section: Model Data and Methodologymentioning
confidence: 99%
“…However this causal relationship is strong in case of developing countries as compare to advance countries. Tahir (2008) did study in Pakistan and concluded that there is unidirectional causality running from economic development to financial development both in short run and long run. Real per capita GDP was used as a proxy of economic development while ratio of domestic credit to GDP, total capital formation to GDP, weighted average savings interest rate minus current GDP deflator and GDP deflator were used for financial development.…”
Section: Studies Related To Bank's Deposits and Economic Growthmentioning
confidence: 99%
“…With respect to Pakistan majority of empirical studies (e.g., Jalil & Ma, 2008;Khan et al, 2005;Mahmood, 2013;Naveed & Mahmood, 2019;Tahir, 2008) have used linear approach to detect the relationship between financial development and economic growth. However, inferences based on the linear relationship become defunct after the structural changes in the form of financial sector reforms initiated in Pakistan in the early 1990s.…”
Section: Introductionmentioning
confidence: 99%